Experimental investigation of French bread baking under conventional conditions or short infrared emitters. (22nd January 2015) - Ploteau, J.P.; Glouannec, P.; Nicolas, V.; Magueresse, A.
Abstract: The objective of this study is to improve energy efficiency of an oven used for the conventional baking of French bread. Experiments performed to validate a numerical model and test different infrared emitters are presented. In order to provide a relevant experimental database, we first instrumented an industrial electrical static oven. The modifications made to the oven and instrumentation installed allows monitoring baking kinetics. The quantities measured are bread mass, temperature field, volume expansion and pressure. An energy balance is calculated to define the energy necessary to cook one "baguette". Heat is provided by natural convection, direct conduction and mainly by infrared radiation to the dough. To improve energy efficiency, short infrared emitters are arranged on the vault instead of traditional electrical resistances made of reinforced metal alloy. These emitters allow increasing radiation heat transfer. Then, baking under short infrared emitters is carried out at lower air temperature, for the same total baking time. Energy consumption is analyzed and compared in both cases. Highlights: Improve energy efficiency of bread baking oven. Characterization of traditional baking with steam injection. Comparison between two heating techniques: conventional or short infra-red emitter. Energy supply is compared for the baking of one baguette. Low temperature baking under infrared emitters leads to 20% energy saving.